Bruce Campbell calls for revolt and revolution - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Early in the morning on Saturday November 15th, in a crowded auditorium, Bruce Campbell delivered an inspiring presentation, to round up what had been an inspiring morning of presentations from youth from all around the world, working with tools as diverse as GIS, facebook and MTV to tackle the challenges presented by climate change for agriculture and forestry. You can watch the full session here: http://youtu.be/nTbdodRkYWU